2014
DOI: 10.1002/pca.2501
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Solid-Phase Extraction Followed by HPLC-ESI/QTOF/MS/MS for Rapid Screening and Structural Identification of Trace Diterpenoids in Flowers of Rhododendron molle

Abstract: By qualitative research of diterpenoids in this plant by HPLC-ESI/QTOF/MS/MS, a reliable methodology for the analysis of these active constituents of R. molle was established for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Thus, the structure of 17 was elucidated as 3β-[(β- d -glucopyranosyl)­oxy]-2α,5β,­6β,­10α,14β,16α-hexa­hydroxy­grayanane. This structure was reported recently by Kong’s group in a rapid screening of R. molle and was identified tentatively based on MS fragmentation analysis …”
Section: Resultsmentioning
confidence: 54%
“…Thus, the structure of 17 was elucidated as 3β-[(β- d -glucopyranosyl)­oxy]-2α,5β,­6β,­10α,14β,16α-hexa­hydroxy­grayanane. This structure was reported recently by Kong’s group in a rapid screening of R. molle and was identified tentatively based on MS fragmentation analysis …”
Section: Resultsmentioning
confidence: 54%
“…Limonoids have moderate polarity and are concentrated in the crude extract for possible separation using an ODS‐SPE column according to polarity. This process has often been used in sample pretreatment methodologies 22–24 …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of their NMR data (Tables 2 and 3) revealed that micranthanoside H (13) differed from the known rhodomoside A (16) 7 by the presence of a tetrasubstituted double bond (δ C 125.5, C-10; 138.1, C-9) in 13, instead of the exocyclic double bond (δ H 5.03, s; 5.01, s, H 2 -20; δ C 113.8, C-20; 152.4, C-10) in 16. The HMBC correlations from H 3 -20 (δ H 1.69, s) to C-9 (δ C 138.1), C-10 (δ C 125.5), and C-1 (δ C 44.9) revealed the position of the tetrasubstituted Δ 9 (10) double bond. Thus, the structure of compound 13 was defined as 3β-(β-D-glucopyranosyloxy)-5β,6β,14β,16α-tetrahydroxygrayan-9(10)-ene.…”
Section: Journal Of Natural Productsmentioning
confidence: 98%
“…To date, more than 100 grayanane diterpenoids have been reported from nature; however, grayanane diterpenoid glucosides are relatively rare. Since the first grayanane diterpenoid glucoside, grayanoside A, was isolated from Leucothoe grayana in 1978, only a total of 23 grayanane diterpenoid glucosides have been reported from the Ericaceae plants, namely, grayanosides A–D, craiobiosides A and B, rhodomosides A–F, , 1β-rhodomoside B, rhojaponin VI-3-glucoside, , pierosides A and C, pierisformosides A–C, , pierisformosides H and I, 3β-(β- d -glucopyranosyloxy)-5β,6β,10α,16β-tetrahydroxygrayan-9­(11)-ene, and rhododeoside I . Among them, craiobioside A and rhojaponin VI-3-glucoside were reported to show significant antinociceptive activity …”
mentioning
confidence: 99%